THE IMPLEMENTATION OF ASEAN SECURITY COMMUNITY PILLAR IN COMBATING THE TRANSNATIONAL CRIME IN SOUTHEAST ASIA - Elida Rahajeng Puspitasari (FH 16 UMY 028, 2016)
Globalization has successfully given an impact to the development of the transnational crime in Southeast Asia. Its impact to the Southeast Asian countries grows rapidly after the cold war. The appearance of transnational crime which is considered as the non-traditional threat can be in the form of Terrorism, Human Trafficking, and Illicit Drugs trafficking. Those three issues are considered as the majority crime in Southeast Asia. In combating the transnational crime, the security region has to be strengthened through the implementation of ASEAN Security Community pillar which is one of the ASEAN Community pillars which has been implemented by the end of 2015. One of the actions in combating the transnational crime in Southeast Asia was envisaged on the Blueprint of ASEAN Security Community. The Blueprint contains the action of plan that has to be taken by the ASEAN members in facing the threats which endanger the security and stability of the region. The paper aims to elaborate the importance of security pillars’ implementation in combating the transnational crime in Southeast Asia and the challenges faced by Southeast Asian Countries dealing with the issue of security in Southeast Asia. By using normative legal and descriptive qualitative method, the research found that the challenge faced by ASEAN comes from the inside body of ASEAN itself. The challenge is the ASEAN members can’t fully implement the terms contained in the ASEAN Security Community Blueprint in order to combat the non-traditional threat. In order to face the challenge, ASEAN needs to implement what have been declared in the Blueprint of ASEAN Security Community to enhance the security order. Keywords: Security Community, Blueprint of ASEAN Security Community, Transnational Crime.